Quantitative Monitoring of Intravascular Coagulation and Fibrinolysis in the Lungs of Rats - Coombey, D; Tyler, H. M (Thrombosis and Haemostasis, 1972)
A method is described whereby the arrival and subsequent lysis of thrombin- induced, 125I-labelled, pulmonary emboli can be quantitatively monitored in the rat. A scintillation probe placed over one lung monitors radioactivity in that organ ; serial counts or a continuous recording of radioactivity can be made. Radioactivity counted in serial blood samples also reflect the defibrination and fibrinolytic processes. The influence of the inhibitor EACA, and the lytic agent Brinase are described.